The Child-Centered Family: Impotence and Despair - Martín Alonso, Helena; Pizarroso, Marta; Sánchez García, Ana (Cuadernos de Trabajo Social, 2013)
Working from the idea that school absenteeism is a signal that talks about difficulties in the family, this article seeks to explain, through four cases, family relational characteristics and to understand the role that absenteeism plays. We examine the framework and context of action and how they determine the interventions. We believe it is necessary to broaden a vision to introduce possibilities to facilitate performances based on the family systems model, analyzing parenting styles and family structure, thus facilitating the work on relationships and interactions of family members.
Keywords: absenteeism; family structure; parenting styles; family relationships